Exploring fire adaptation in a land with little fire: serotiny in Leptospermum scoparium (Myrtaceae). (4th April 2017) - Battersby, Paul F.; Wilmshurst, Janet M.; Curran, Timothy J.; McGlone, Matthew S.; Perry, George L. W.
Abstract: Aim: Immigrant floras often have distinctive traits, well suited to the host region but absent from the autochthonous flora. An example is serotiny in the New Zealand (NZ) small tree, Leptospermum scoparium (Myrtaceae) belonging to a strongly fire‐adapted Australian clade. Serotiny in L. scoparium has been attributed either to strong selection by fire since human settlement, or taken as evidence that pre‐human fire in NZ was more important than assumed. By integrating field data, experimental analyses and long‐term fire histories, we sought to explain the spatial pattern of serotiny in L. scoparium in NZ, and evaluate these two explanations. Location: New Zealand. Methods: We quantified the distribution of serotiny in L. scoparium by analysing 137 populations distributed across NZ (two previous studies and ours), including 31 with Holocene fire histories. We assessed the relationship of serotiny with a suite of fire and climate environmental predictors, and between serotiny and shoot‐level flammability. Results: Serotiny was strongly positively associated with latitude (more in the north), lower rainfall and higher temperatures. Serotinous populations were rare at sites with no history of fire. Serotiny was most prevalent in northern wetlands, where fire was recurrent during the Holocene, but was nearly absent from the southwestern Southern Alps. Shoot‐level flammability and serotiny were not correlated. Main conclusions: The distribution of serotiny in L. scoparium relates not only to current environments but also to the legacy of regional shifts in vegetation during Quaternary glacial–interglacial cycles. Serotiny was maintained where the landscape experienced sporadic fire, but it is absent from NZ's southern South Island because the sparse, open vegetation during the glacials did not support fire. Serotinous L. scoparium populations were therefore more common in the northern North Island. Human transformation of the fire regime over the last 750 years has likely favoured the spread of serotinous populations.